Analysis of Marketing Features in Russia in the Context of Digitalization - P. V. Evstigneeva (Мир новой экономики, 2022)
In the modern world, constantly changing business trends require more attention to promoting the brand and attracting an audience. The need to study and analyze the effects of marketing tools and tools has increased significantly with the advent of digital technologies. In response to the daily challenges associated with the changing level of competition in the market, globalization, and consumer awareness, small and medium-sized businesses are forced to adapt. There is a change in the course of conducting the promotion policy, and preference is given to the Internet space. In this regard, new platforms for market relations come to the fore. For entrepreneurs, the question arises “how?” and “where?” should they conduct their activity. The article discusses the features of the trend of transition to Internet marketing and the results of scientific research. Also, the author considered the issue of the relevance of digital promotion tools.